Analisis Realisasi Anggaran Belanja Pada Kantor Lapas Kelas II-A Banda Aceh - Zulkifli Umar; Yusliana; Fahri Ulya (Asosiasi Dosen dan Praktisi Ekonomi Nusantara, 2025)
This study aims to find out the realization of the budget at the Class II A Prison Office in Banda Aceh in 2016-2018. This study uses a qualitative descriptive method. Data collection is carried out by means of library research and field research. The object of this research is the Class II A Prison Office in Banda Aceh. Based on the results of the study, it is known that: (1) The realization of the budget of the Class II A Prison Office of Banda Aceh based on the analysis of the effectiveness ratio of the Fiscal Year 2016-2018 in the Effective category with an effectiveness value of 97.18% in 2016, 99.91% in 2017, and 99.63% in 2018, and (2) The realization of the budget of the Class II A Prison Office in Banda Aceh based on the analysis of the efficiency ratio of the Fiscal Year 2016-2018 in the Inefficient category with a value of efficiency of 102.90% in 2016, 100.09% in 2017, and 100.37% in 2018